1993
DOI: 10.1007/bf00454891
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent histochemical localization of lipid peroxidation during brain reperfusion following cardiac arrest

Abstract: Rats were subjected to cardiac arrest and resuscitation, 90 min of reperfusion, and in situ perfusion fixation. Thiobarbituric acid (TBA) was included in the aldehyde-free perfusion fixative, the TBA reaction was driven in situ by heating, and fluorescence microscopy was utilized to characterize the location of products of the TBA reaction. Absorbance-difference spectra were performed on butanol-extracted brain homogenates to confirm in situ formation of TBA adducts with aldehydic products of lipid peroxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 46 publications
1
18
0
1
Order By: Relevance
“…Significance is also attached to the LM observation that these neurons revealed morphological features consistent with irreversible damage, including cellular distortion, vacuolization, and pyknotic nuclei. The parallel EM findings of increased electron density, together with the dilation of the Golgi and SER and increased numbers of dilated vesicles, were also consistent with a necrotic cascade triggered by the translocation of lysosomal cathepsins and other hydrolytic enzymes (White et al, 1993;Chan, 1996;Yamashima et al, 1998;Yamashima, 2004). However, we cannot rule out that this organelle and vesicular dilation are linked to an albeit abortive attempt at membrane repair mediated by the lysosomes and the synaptotagmin found on their surfaces (Andrews, 2005).…”
Section: Membrane Disruption and Enduring Membrane Permeabilitymentioning
confidence: 52%
“…Significance is also attached to the LM observation that these neurons revealed morphological features consistent with irreversible damage, including cellular distortion, vacuolization, and pyknotic nuclei. The parallel EM findings of increased electron density, together with the dilation of the Golgi and SER and increased numbers of dilated vesicles, were also consistent with a necrotic cascade triggered by the translocation of lysosomal cathepsins and other hydrolytic enzymes (White et al, 1993;Chan, 1996;Yamashima et al, 1998;Yamashima, 2004). However, we cannot rule out that this organelle and vesicular dilation are linked to an albeit abortive attempt at membrane repair mediated by the lysosomes and the synaptotagmin found on their surfaces (Andrews, 2005).…”
Section: Membrane Disruption and Enduring Membrane Permeabilitymentioning
confidence: 52%
“…De Duve and Wattiaux (1966) first reported that the lethal cell injury occurs by the release of hydrolytic enzymes from damaged lysosomes. Spreading of hydrolytic enzymes into the cytoplasm by the lysosomal membrane injury or rupture, was confirmed in both heart (Brachfeld, 1969;Ichihara et al, 1987;Molchanova et al, 1991) and brain (White et al, 1992;Chan, 1996) ischemic injuries. The translocation of cathepsin B from lysosomes to cytosol and nucleus was confirmed also in the bile salt-induced and tumor necrosis factor (TNF)-triggered hepatic apoptosis Guicciardi et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…40 The lysosomal enzymes are involved in autophagic activity. Spreading of hydrolytic enzymes from lysosomes into the cytoplasm due to the lysosomal membrane injury or rupture had been suggested in both heart 49-51 and brain 52,53 ischemic injuries. The lysosomal system could contribute to cell death in the following ways: (1) rupture of the lysosome, (2) excess of autophagy, (3) accumulation of secondary lysosomes or residual bodies, or (4) lysosome dysfunction.…”
Section: Discussionmentioning
confidence: 99%